Effect of tonsillectomy with or without adenoidectomy on formant sound frequency - Rianto, Bambang Udji Djoko; Jenny, .; Indrasari, Sagung Rai (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
ABSTRACT Vocal tract resonance characteristics are reflected by formant frequencies which determined by the size and shape of the vocal tract. Tonsillectomy may cause changes in the structure of the oral cavity as a resonator in the speech process. The aim of this study is to determine the effect of tonsillectomy on formant sound frequency. This study used a pre-test and post-test only design experimental. The study underwent in the Otorhinolaryngology Department between August up to November 2012. Inclusion criteria were: 1) chronic tonsillitis, 2) tonsil size was T3-T4, 3) age up to 5 years. The exclusion criteria were craniofacial abnormality and neurological disorders. All patients performed a sound analysis by recording vowel / a /, / e /, / i /, / o /, and / u / in 1 day before and 4 weeks after surgery. The sample consisted of 24 (60%) women and 16 (40%) men. The T3-T3 tonsil size were 25 (62.5%) samples and the lowest than T3-T4/T4-T3 were 6 (15%) samples. Based on paired T test there was a statistically significant increase of all F1 vowels (p <0.05), except for / i / (p> 0,05) and decrease of F2 / e / and F3 / u / (p >0,05). Based on these results it can be concluded that tonsillectomy affects the F1 mean difference almost in all vowel except the vowels / i /, F2 & F3.